2021
DOI: 10.1186/s12885-021-08138-3
|View full text |Cite
|
Sign up to set email alerts
|

PIVKA-II serves as a potential biomarker that complements AFP for the diagnosis of hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common malignant tumors of the digestive system and has high morbidity and mortality rates. It is essential to search new biomarkers to improve the accuracy of early HCC diagnosis. Therefore, we evaluated the diagnostic value of prothrombin induced by vitamin K deficiency or antagonist- II (PIVKA-II) as a potential biomarker that complements α-fetoprotein (AFP) in HCC by detecting the serum PIVKA-II levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 30 publications
9
67
0
1
Order By: Relevance
“…Patients with high serum AFP levels also had higher serum PIVKA-II. PIVKA-II is usually used in addition to AFP measurement for HCC diagnosis [ 42 ]. However, in this study, we found that there was a positive association between serum AFP and PIVKA-II levels in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high serum AFP levels also had higher serum PIVKA-II. PIVKA-II is usually used in addition to AFP measurement for HCC diagnosis [ 42 ]. However, in this study, we found that there was a positive association between serum AFP and PIVKA-II levels in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…PIVKA-II is another widely used HCC marker with high specificity. PIVKA-II is a powerful supplement to AFP in HCC diagnosis [ 35 ], and their combination could improve the accuracy [ 35 38 ]. Recent reports have suggested that the ratio of gamma-glutamyltransferase to aspartate aminotransferase (γ-GT/AST) and the Lens culinaris agglutinin-reactive fraction of AFP (AFP-L3) are valuable markers in HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The well-established biomarker AFP evaluated in many studies had high proportions of false positives. The novel biomarker PIVKA-II had better diagnostic performance with higher specificity in HCC early detection despite the conditions including vitamin K deficiency, malnutrition, drug (e.g., warfarin), and obstructive jaundice ( 64 , 70 , 71 ). In addition, the mechanism of PIVKA-II and AFP was independent.…”
Section: Clinical Relevance Of Pivka-ii In Hccmentioning
confidence: 99%